THE EFFECT OF OWNERSHIP CONCENTRATION, CASH HOLDING ON COMPANY VALUE WITH DIVIDEND PAYOUT RATIO AS AN INTERVENING VARIABLE - Septianar Sitorus; Thezar Fiqih Hidayat Hasibuan; Minda Muliana Br Sebayang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of Ownership concentration (X1) and Cash holding (X2) on Company Value (Y) which is proxied by the Price earning ratio through the Dividend payout ratio (Z) as an intervening variable. The population used is all Coal sub-sector companies listed on the Indonesia Stock Exchange in 2019-2022. The sample of this study was 9 companies using purposive sampling. The data collection method is the documentation study method, literature method and research gap and is analyzed quantitatively. The data analysis method is Path Analysis with the help of Smart PLS version 3 with the PLS test method consisting of the Outer Model Analysis test, Inner Model Analysis, and Hypothesis Testing. This study concludes that (1) Ownership concentration has a significant positive effect on company value, (2) Cash holding has a significant positive effect on company value, (3) Ownership concentration does not have an effect on the dividend payout ratio, (4) Cash holding has a significant positive effect on the dividend payout ratio, (5) Dividend payout ratio has a significant effect on company value, (6) Ownership concentration does not have an effect on company value through the mediation of dividend payout ratio, (7) Cash holding has a significant positive effect on company value through the mediation of dividend payout ratio.